2023
DOI: 10.1002/ana.26604
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Eye Movement Sleep, Neurodegeneration, and Amyloid Deposition in Aging

Abstract: Rapid eye movement (REM) sleep is markedly altered in Alzheimer's disease (AD), and its reduction in older populations is associated with AD risk. However, little is known about the underlying brain mechanisms. Our objective was to investigate the relationships between REM sleep integrity and amyloid deposition, gray matter volume, and perfusion in aging. Methods: We included 121 cognitively unimpaired older adults (76 women, mean age 68.96 AE 3.82 years), who underwent a polysomnography, T1-weighted magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
11
2
Order By: Relevance
“…24,25 Alternatively, REM sleep may be an important regulator of Alzheimer pathology and neurodegeneration. 26 DORAs increase REM sleep more than other hypnotics, 27 although we did not find an increase in REM sleep in the groups treated with suvorexant. Based on these prior results, our findings, and the observation that the effect of suvorexant persisted for > 18 hours after drug administration, we hypothesize that suvorexant's effect on p-tau and Aβ may be due to mechanisms other than sleep involving orexin receptor signaling pathways, although further studies are needed.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…24,25 Alternatively, REM sleep may be an important regulator of Alzheimer pathology and neurodegeneration. 26 DORAs increase REM sleep more than other hypnotics, 27 although we did not find an increase in REM sleep in the groups treated with suvorexant. Based on these prior results, our findings, and the observation that the effect of suvorexant persisted for > 18 hours after drug administration, we hypothesize that suvorexant's effect on p-tau and Aβ may be due to mechanisms other than sleep involving orexin receptor signaling pathways, although further studies are needed.…”
Section: Discussioncontrasting
confidence: 62%
“…A potential explanation of these findings is that previous studies in a diurnal species of monkeys found that the administration of GHB at night did not change CSF orexin levels, 24 whereas sleep deprivation increased CSF orexin levels 24,25 . Alternatively, REM sleep may be an important regulator of Alzheimer pathology and neurodegeneration 26 . DORAs increase REM sleep more than other hypnotics, 27 although we did not find an increase in REM sleep in the groups treated with suvorexant.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…[21][22][23] Further, 1 study linked REM sleep microstructure to amyloid deposition in older adults. 24 Studies, including ours, have failed to demonstrate an association between SWS percentage measured at a single time point and risk of cognitive decline or dementia. 25,26 Thus, it may be the decline in SWS percentage, rather than individual differences at a given time, that are important for determining dementia risk.…”
Section: Discussionmentioning
confidence: 58%
“…Some studies have shown associations between slow-wave activity and amyloid burden in humans whereas others suggest that sleep spindle–slow wave coupling, rather than the quantity of overnight slow waves per se, is associated with amyloid accumulation . Further, 1 study linked REM sleep microstructure to amyloid deposition in older adults . Studies, including ours, have failed to demonstrate an association between SWS percentage measured at a single time point and risk of cognitive decline or dementia .…”
Section: Discussionmentioning
confidence: 62%